HUBUNGAN EFIKASI DIRI DAN KEPUASAN KERJA DENGAN OCB PADA GURU DI SMP NEGERI SE-KECAMATAN LOGAS TANAH DARAT - Wenni Kapriana Perta; Isjoni Isjoni; Hasnah Faizah AR (Universitas Riau, 2017)
The purpose of this study is to reveal the relationship between Self Efficacyand Job Satisfaction with OCB in Junior High School Teachers in Logas Tanah Darat Subdistrictof Kuantan Singingi Regency. This research uses survey method with correlinonal technique.The research variable consists of two independent variables: Self Efficacy X1) and jobsatisfaction (X2) while the dependent variable is OCB (Y). The data source of this research isthe teachers of SMP Negeri Se-Kecamatan Logas Tanah Darat which amounts to 91 people.The result of the research shows there is a positive relationship between Self Efficacy withOCB with correlation coefficient of 0. 728. The relationship between job satisfaction withOCB is also positive at 0.466. While the relationship between Self Efficacy and job satisfactionwith OCB SMP Negeri in Kecamatan Logas Tanah Darat Kuantan Singingi District can beseen that the value of R Square = 0.551 or 55.1%. So the strength of self efficacy relationshipand job satisfaction with OCB teachers amounted to 55.1%. It can be concluded that thestrength of the relationship between independent variables with the dependent variable in themedium category. The conclusions of the Self Efficacy (X1) and Job Satisfaction (X2) variableswith OCB (Y) have a positive direction.